2018
DOI: 10.3389/fmicb.2018.02587
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance in Toxoplasma gondii

Abstract: Toxoplasma gondii (T. gondii) is a global protozoan parasite infecting up to one-third of the world population. Pyrimethamine (PYR) and sulfadiazine (SDZ) are the most widely used drugs for treatment of toxoplasmosis; however, several failure cases have been recorded as well; suggesting the existence of drug resistant strains. This review aims to give a systematic and comprehensive understanding of drug resistance in T. gondii including mechanisms of resistance and sites of drug action in parasite. Analogous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 80 publications
1
122
0
4
Order By: Relevance
“…In the context of congenital transmission, when a woman gets the infection during pregnancy, recommended drugs for treatment are limited to a combination of sulfadiazine plus pyrimethamine (SDZ + PYR) and spiramycin 8 , 19 , 20 , 24 . Unfortunately, the use of these drugs has been associated with severe side effects and uncommon reactions in both mother and child 3 , 27 , 56 . Additionally, several independent studies have shown that T. gondii has an exceptional adaptive potential, which has led to the development of drug-resistant parasites 56 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of congenital transmission, when a woman gets the infection during pregnancy, recommended drugs for treatment are limited to a combination of sulfadiazine plus pyrimethamine (SDZ + PYR) and spiramycin 8 , 19 , 20 , 24 . Unfortunately, the use of these drugs has been associated with severe side effects and uncommon reactions in both mother and child 3 , 27 , 56 . Additionally, several independent studies have shown that T. gondii has an exceptional adaptive potential, which has led to the development of drug-resistant parasites 56 58 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been observed that about 40% of patients were forced to stop therapy due to low tolerance and serious adverse effects (Porter and Sande, 1992;McLeod et al, 2006;Rajapakse et al, 2013). In addition, drug resistance cases are being reported in some cases of toxoplasmosis (Montazeri et al, 2018). Also, there are no approved therapies for the eradication of the encysted bradyzoite form.…”
Section: Introductionmentioning
confidence: 99%
“…Human can be infected with T. gondii through one of three ways: 1) by eating raw or undercooked meat containing T. gondii tissue cysts or eating food that has been cross-contaminated with raw/undercooked meat; 2) by ingesting oocysts from soil (through gardening, handling/eating unwashed vegetables, or infected cat feces); or 3) by acquiring congenital infection through the placenta [4,5] when a woman gets an infection during pregnancy [6,7] In most cases, infection in humans is asymptomatic or mild symptoms including malaise, swelling of lymph nodes and fever [8], however, when infection occurs in pregnant women several health problems can affect the fetuses, including mental retardation, blindness, epilepsy, abortion and death [1,9]. Moreover, In a systematic review and meta-analysis, it was reported that T. gondii causes severe encephalitis via acute infection or reactivation of latent infection among immune-suppressed individuals, including those with acquired immunodeficiency syndrome (AIDS), immunosuppressive cancer, and transplant recipients on immunosuppressive drugs [10].…”
Section: Introductionmentioning
confidence: 99%